Preparation method of calcium-based polymeric ferric sulfate titanium

By doping calcium and titanium elements into polymeric iron sulfate, calcium-based polymeric iron sulfate products are prepared, which solves the problems of insufficient stability and coagulation performance of existing products, and achieves efficient water treatment effects and optimized utilization of resources.

CN119797436APending Publication Date: 2025-04-11EAST CHINA UNIV OF SCI & TECH +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510013482.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-06
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The existing polymeric ferrous sulfate products still have room to improve their stability and coagulation performance, and the treatment and resource utilization of ferrous ferrous sulfate lies in resource waste and environmental protection risks.

Method used

By doping calcium and titanium elements into polymeric iron sulfate, calcium-based polymeric iron sulfate products are prepared, and the titanium elements contained in ferrous ferrous yellow can significantly improve the coagulation effect of the product and reduce production costs.

Benefits of technology

It significantly improves the stability and coagulation performance of polymeric iron sulfate products, meets higher standards, and realizes efficient utilization of resources, reducing production costs and environmental pressure.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119797436A_ABST
    Figure CN119797436A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of calcium-based polymeric ferric sulfate titanium, which comprises the following steps: adding a calcium-based modifier and a titanium-based modifier into a polymeric ferric sulfate liquid product, heating and stirring to obtain a modified liquid product; and drying to prepare the solid calcium-based polymeric ferric sulfate titanium. The polyferric sulfate liquid product can be prepared from ferrous sulfate monohydrate or by taking a byproduct yellow ferrous iron of titanium dioxide prepared by a sulfuric acid method as a raw material through oxidation, hydrolysis and polymerization reaction, and when the yellow ferrous iron is taken as the raw material, the titanium element contained in the yellow ferrous iron can be directly utilized for modification. Polyferric sulfate is modified by doping calcium and titanium elements, the calcium-based polymeric ferric sulfate titanium product is successfully developed, the coagulation effect of the polymeric ferric sulfate product can be remarkably improved, meanwhile, the production cost of the polymeric ferric sulfate product is reduced, and the economic benefits of enterprises are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of comprehensive utilization of industrial solid waste resources, and relates to a modification method of polyferric sulfate, and specifically, to a preparation method of calcium-based polyferric titanium sulfate. Background Art

[0002] Polyferric sulfate (PFS) is a coagulant used in water treatment. It has strong flocculation and sedimentation properties. It can effectively remove suspended matter, colloids and certain organic pollutants in water and improve water clarity. Compared with traditional ferric sulfate, PFS exhibits better sedimentation and a wider pH adaptability during the treatment process. It can work efficiently in the acidic to neutral pH range and has a good removal effect on organic matter and microorganisms in water. In addition, the use of PFS is low, which can reduce treatment costs and reduce the generation of waste residues. Due to its excellent performance, PFS is widely used in drinking water, industrial wastewater and municipal sewage treatment.

[0003] Ferrous yellow, whose main component is ferrous sulfate monohydrate, is a solid waste product produced by the concentration of waste acid in the titanium dioxide production process. It is rich in a large number of iron, sulfur, oxygen, titanium and other elements. Based on the annual production capacity of 150,000 tons of titanium dioxide, 135,000 tons of ferrous yellow can be generated each year. At present, ferrous yellow is mainly processed by co-firing to prepare sulfuric acid and by lime neutralization. Among them, the co-firing acid production method is limited by the equipment production capacity, and the amount of ferrous yellow consumed each year is limited. The remaining ferrous yellow is neutralized with lime and piled up in the form of solid slag. This not only increases the processing cost, but also leads to resource waste and environmental risks.

[0004] CN116654992A discloses a method for producing polyferric sulfate using ferrous yellow. The method uses ferrous yellow as a raw material, adds red iron oxide to neutralize the free acid in ferrous yellow, and prepares polyferric sulfate through oxidation, hydrolysis and polymerization. However, the stability and coagulation performance of PFS currently produced by ferrous yellow and conventional commercially available PFS such as ferrous sulfate monohydrate still need to be further improved, and how to reduce environmental pollution, improve the economic benefits and production benefits of enterprises, and thus enhance market competitiveness, is also a technical problem that needs to be solved in this field.

[0005] The stability and coagulation performance of PFS are mainly measured by basicity and turbidity removal rate. Basicity is the ratio of alkaline components to acidic components in the coagulant, which is specifically reflected in the OH - with Fe 3+ In general, the higher the basicity of PFS, the longer its molecular chain is, and the stronger its net-catching effect on pollutant particles is. However, too high a basicity will increase the Fe 3+The hydrolysis degree of PFS will reduce the stability of the product. Therefore, the national standard requires that the basicity of PFS should be between 8% and 16%. The turbidity removal rate directly reflects the removal effect of turbid substances in water after coagulation treatment and is a key indicator for evaluating the coagulation performance of PFS. On the basis of ensuring stability, how to further improve the coagulation effect of PFS is still a core problem that needs to be solved urgently. Summary of the invention

[0006] The purpose of the present invention is to further improve the coagulation effect of polyferric sulfate products, and to find a preparation method of polyferric sulfate with strong stability and better coagulation effect. The present invention modifies polyferric sulfate, and successfully develops a calcium-based polyferric sulfate titanium product by doping calcium and titanium elements. For polyferric sulfate prepared from ferrous iron, the modification can directly utilize the titanium element contained therein, which can significantly improve the coagulation effect of the polyferric sulfate product while reducing its production cost, thereby improving the economic benefits of the enterprise.

[0007] To achieve the above object, the first aspect of the present invention provides a method for preparing calcium-based polyferric titanium sulfate, comprising the following steps:

[0008] S1. Adding a calcium-based modifier and a titanium-based modifier to a polymerized ferric sulfate liquid product for modification, heating and stirring to obtain a modified liquid product;

[0009] S2. Drying the liquid product obtained in step S1 to prepare solid calcium-based polyferric titanium sulfate.

[0010] According to a preferred embodiment of the present invention, the molar ratio of the calcium-based modifier to the iron raw material for preparing the polyferric sulfate liquid product is 1:0.01-0.04; the mass ratio of the titanium-based modifier to the iron raw material for preparing the polyferric sulfate liquid product is 1:0.001-0.04.

[0011] Furthermore, the calcium-based modifier is selected from one or more of anhydrous calcium chloride, dihydrate calcium chloride, calcium oxide, and calcium hydroxide.

[0012] Furthermore, the titanium-based modifier is selected from one or more of titanyl sulfate, metatitanic acid, titanium chloride, titanium dioxide, and titanium powder.

[0013] According to a preferred embodiment of the present invention, the heating temperature for modification in step S1 is 55-70° C., and the reaction time is 20-90 min; the drying temperature in step S2 is 60-80° C., and the drying time is 24-48 h.

[0014] The second aspect of the present invention provides a method for preparing calcium-based polyferric titanium sulfate, comprising the following steps:

[0015] S0, dissolving the yellow ferrous iron produced as a by-product of the sulfuric acid process titanium dioxide in water, adding an iron source and stirring, then adding an oxidant, heating and stirring, and performing oxidation, hydrolysis, and polymerization reactions to obtain a liquid polymerized ferric sulfate product;

[0016] S1. Adding a calcium-based modifier to a polyferric sulfate liquid product, heating and stirring to obtain a modified liquid product;

[0017] S2. Drying the liquid product obtained in step S1 to prepare solid calcium-based polyferric titanium sulfate.

[0018] According to a preferred embodiment of the present invention, the molar ratio of the calcium-based modifier to ferrous iron is 1:0.01-0.04.

[0019] Furthermore, the calcium-based modifier is selected from one or more of anhydrous calcium chloride, dihydrate calcium chloride, calcium oxide, and calcium hydroxide.

[0020] According to a preferred embodiment of the present invention, the heating temperature for modification in step S1 is 55-70° C., and the reaction time is 20-90 min; the drying temperature in step S2 is 60-80° C., and the drying time is 24-48 h.

[0021] The third aspect of the present invention provides a calcium-based poly-iron titanium sulfate prepared according to the above method.

[0022] Compared with the prior art, the present invention has the following beneficial effects:

[0023] (1) Based on the traditional polyferric sulfate preparation technology, the present invention modifies it by doping calcium and titanium elements, and successfully develops a calcium-based polyferric sulfate titanium product. This modification treatment not only makes the final product meet the requirements of the first-class products in the GB / T14591-2016 standard, but also significantly improves its performance in many aspects. Specifically, the modified product has a higher basicity, a more significant polymerization effect, and exhibits better stability and coagulation performance. These improvements not only improve the comprehensive performance of the product, but also reduce production costs while ensuring the efficiency and reliability of the product in practical applications, thereby achieving a dual improvement in economic benefits and performance advantages.

[0024] (2) The present invention uses titanium dioxide solid waste yellow ferrous iron as a production raw material, utilizes the titanium element contained in yellow ferrous iron, and adds a cheap and easily available calcium-based modifier to prepare a calcium-based polyferric sulfate titanium modified product, which not only effectively solves the problems of large solid waste treatment volume and high treatment costs, but also realizes the resource utilization of solid waste. This method significantly alleviates the environmental pressure of solid waste treatment by converting solid waste into valuable products, and at the same time brings economic benefits to enterprises. The resource treatment of solid waste not only reduces the treatment cost, but also optimizes the recycling of resources, achieving a win-win situation for environmental protection and economic growth. The product significantly improves the turbidity removal rate, making it more superior in actual water sample treatment applications. In addition, the product has a high total iron content, excellent polymerization degree, and enhanced stability and coagulation performance. These improvements not only improve the technical performance of the product, but also expand its application potential in various water treatment scenarios, providing the industry with an efficient and economical solution. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 This is a process flow chart for the preparation of calcium-based polyferric titanium sulfate.

[0026] Figure 2 The present invention is a process flow chart for preparing calcium-based polyferric titanium sulfate using ferrous iron as raw material without adding any additional titanium-based modifier. DETAILED DESCRIPTION

[0027] The technical scheme of the present invention is clearly and completely described below with specific embodiments. It should be understood that the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of the present invention.

[0028] The polyferric sulfate system used in the following embodiments is prepared according to conventional methods known in the art, usually using ferrous sulfate monohydrate or ferrous yellow, a byproduct of titanium dioxide produced by the sulfuric acid process, as the iron raw material, and is prepared by oxidation, hydrolysis, and polymerization reactions:

[0029] 1. Preparation method using ferrous sulfate monohydrate as iron raw material:

[0030] 90% (mass fraction) FeSO4·H2O is dissolved in a small amount of water, 98% (mass fraction) sulfuric acid is added to the system at a mass ratio of 1:0.16, 30% hydrogen peroxide solution is added dropwise to the system at a mass ratio of 1:0.4, and the mixture is stirred and reacted at 55°C for 90 minutes to obtain a liquid polyferric sulfate product, namely the polyferric sulfate system.

[0031] 2. Preparation method using ferrous yellow, a byproduct of titanium dioxide produced by the sulfuric acid process, as iron raw material:

[0032] Ferrous iron (FeSO4·H2O content of about 61%, titanium content of about 4%) was dissolved in water and put into a reactor with iron powder in a molar ratio of 1:0.24, stirred and reacted at 55°C for 15 minutes, and 30% (mass fraction) hydrogen peroxide solution was added dropwise to the system at a mass ratio of 1:0.4, stirred and reacted at 55°C for 90 minutes to obtain a liquid polymerized ferric sulfate product.

[0033] The liquid product of polyferric sulfate is prepared from FeSO4·H2O as raw material.

[0034] Example 1

[0035] The polyferric sulfate system used in this embodiment is prepared using ferrous sulfate monohydrate as the iron raw material.

[0036] Anhydrous calcium chloride was added to the polyferric sulfate system at a molar ratio of 1:0.01, and titanyl sulfate was added to the system at a mass ratio of 1:0.04. The reaction was stirred at 55°C for 90 minutes, and the obtained liquid product was vacuum dried at 60°C for 48 hours to obtain a calcium-based polyferric titanium sulfate solid product.

[0037] First-class solid polyferric sulfate reducing material (Fe 2+ The mass fraction of total iron (calculated) must be ≤0.15%, the mass fraction of total iron must be ≥19.5%, and the basicity must be in the range of 8.0% to 16.0%.

[0038] The various indicators of the obtained solid product were analyzed according to the method specified in GB / T 14591-2016, among which the reducing substances (Fe 2+ The mass fraction of total iron is 0.009%, the mass fraction of total iron is 20.21%, and the basicity is 15.05%, all of which meet the requirements of first-class products in GB / T 14591-2016. The turbidity removal rate is 90.03% and the coagulation effect is excellent after the sewage treatment effect evaluation.

[0039] Example 2

[0040] The polyferric sulfate system used in this embodiment is prepared using ferrous sulfate monohydrate as the iron raw material.

[0041] Calcium oxide was added to the polyferric sulfate system at a molar ratio of 1:0.02, and titanium dioxide was added to the system at a mass ratio of 1:0.03. The reaction was stirred at 65°C for 30 minutes, and the obtained liquid product was vacuum dried at 80°C for 24 hours to obtain a calcium-based polyferric titanium sulfate solid product.

[0042] The various indicators of the solid product obtained by analysis all meet the requirements of first-class products in GB / T 14591-2016. The turbidity removal rate is 88.59% after sewage treatment effect evaluation.

[0043] Compared with Example 1, the calcium source in this example is excessive and the titanium source is insufficient. Excess calcium may competitively adsorb or react with the iron ions in PFS, and the introduction of titanium ions has the advantage of increasing the aggregation state of iron. The two synergistically affect the coagulation performance of PFS, so the turbidity removal rate of the product in this example is reduced.

[0044] Example 3

[0045] The polyferric sulfate system used in this embodiment is prepared using ferrous sulfate monohydrate as the iron raw material.

[0046] Calcium chloride dihydrate was added to the polyferric sulfate system at a molar ratio of 1:0.04, and titanic acid was added to the system at a mass ratio of 1:0.02. The mixture was stirred and reacted at 70°C for 20 minutes. The obtained liquid product was vacuum dried at 60°C for 36 hours to obtain a calcium-based polyferric titanium sulfate solid product.

[0047] The various indicators of the obtained solid product were analyzed and all met the requirements of the first-class product in GB / T 14591-2016. The turbidity removal rate was 87.41% after sewage treatment effect evaluation. Compared with Example 2, the calcium source in this example was further increased and the titanium source was further reduced, resulting in a further reduction in the turbidity removal rate of the product.

[0048] Example 4

[0049] The polyferric sulfate system used in this embodiment is prepared using ferrous sulfate monohydrate as the iron raw material.

[0050] Calcium hydroxide was added to the polyferric sulfate system at a molar ratio of 1:0.03, and titanium chloride was added to the system at a mass ratio of 1:0.01. The reaction was stirred at 60°C for 60 minutes. The obtained liquid product was vacuum dried at 70°C for 36 hours to obtain a calcium-based polyferric titanium sulfate solid product.

[0051] The various indicators of the obtained solid product were analyzed and all met the requirements of the first-class product in GB / T 14591-2016. The turbidity removal rate was 86.55% after the sewage treatment effect evaluation. Compared with Example 3, the titanium source in this example was further reduced, and the turbidity removal rate of the product was also reduced accordingly.

[0052] It can be seen from the performance indicators of Examples 1 to 4 that within the range of calcium-iron molar ratio of 1:0.01 to 0.04 and titanium-iron mass ratio of 1:0.01 to 0.04, the product turbidity removal rate is greater than 85%, and the product coagulation effect is relatively excellent.

[0053] Example 5

[0054] The polyferric sulfate system used in this embodiment is prepared using ferrous sulfate monohydrate as the iron raw material.

[0055] Anhydrous calcium chloride was added to the polyferric sulfate system at a molar ratio of 1:0.07, and titanium powder was added to the system at a mass ratio of 1:0.005. The mixture was stirred and reacted at 55°C for 60 minutes. The obtained liquid product was vacuum dried at 60°C for 48 hours to obtain a calcium-based polyferric titanium sulfate solid product.

[0056] The various indicators of the obtained solid product were analyzed and all met the requirements of the first-class product in GB / T 14591-2016. The turbidity removal rate was 83.52% after the sewage treatment effect evaluation. Compared with Example 4, the calcium source in this example was further increased, but the turbidity removal rate of the product did not increase further, but decreased.

[0057] Example 6

[0058] The polyferric sulfate system used in this embodiment is prepared using ferrous sulfate monohydrate as the iron raw material.

[0059] Anhydrous calcium chloride was added to the polyferric sulfate system at a molar ratio of 1:0.09, and titanyl sulfate was added to the system at a mass ratio of 1:0.001. The reaction was stirred at 55°C for 60 minutes, and the obtained liquid product was vacuum dried at 60°C for 48 hours to obtain a calcium-based polyferric titanium sulfate solid product.

[0060] The various indicators of the obtained solid product were analyzed and all met the requirements of the first-class product in GB / T 14591-2016. The turbidity removal rate was 81.79% after sewage treatment effect evaluation. Compared with Example 5, the calcium source in this example was further increased, the titanium source was further reduced, and the turbidity removal rate of the product was further reduced.

[0061] Comparative Example 1

[0062] The various indicators of the obtained solid product were analyzed according to the method specified in GB / T 14591-2016, among which the reducing substances (Fe 2+ The mass fraction of total iron is 21.58%, the basicity is 9.80%, and the turbidity removal rate is 80.58%.

[0063] Comparative Example 1, i.e., the conventional preparation method of commercially available PFS, is compared with the product performance indicators of Examples 1 to 6. It can be seen that, within the range of a calcium-iron molar ratio of 1:0.01 to 0.09 and a titanium-iron mass ratio of 1:0.01 to 0.001, the product polymerization degree of the product modified with titanium calcium using FeSO4·H2O as the raw material is better, the turbidity removal rate is significantly improved, and the coagulation effect is better than that of the commercially available PFS product.

[0064] Comparative Example 2

[0065] The polyferric sulfate system used in this embodiment is prepared using ferrous sulfate monohydrate as the iron raw material.

[0066] Anhydrous calcium chloride was added to the polyferric sulfate system at a molar ratio of 1:0.01, and the mixture was stirred and reacted at 55° C. for 60 min. The obtained liquid product was vacuum dried at 60° C. for 48 h to obtain a calcium-based polyferric titanium sulfate solid product.

[0067] The various indicators of the obtained solid product were analyzed and all met the requirements of the first-class product in GB / T 14591-2016. The turbidity removal rate was 83.41% after the sewage treatment effect evaluation. Compared with Example 1, when no titanium-based modifier was added and only calcium-based modifier was added, the coagulation performance of the product was greatly reduced and the turbidity removal rate was significantly reduced.

[0068] Comparative Example 3

[0069] The polyferric sulfate system used in this embodiment is prepared using ferrous sulfate monohydrate as the iron raw material.

[0070] Titanyl sulfate was added to the polyferric sulfate system at a mass ratio of 1:0.04, and the reaction was stirred at 55°C for 60 minutes. The obtained liquid product was vacuum dried at 60°C for 48 hours to obtain a calcium-based polyferric titanium sulfate solid product.

[0071] The various indicators of the obtained solid product were analyzed and all met the requirements of the first-class product in GB / T 14591-2016. The turbidity removal rate was 82.59% after the sewage treatment effect evaluation. Compared with Example 1, when no calcium-based modifier was added and only titanium-based modifier was added, the coagulation performance of the product was also greatly reduced, and the turbidity removal rate was significantly reduced.

[0072] Comparative Example 4

[0073] The polyferric sulfate system used in this embodiment is prepared using ferrous sulfate monohydrate as the iron raw material.

[0074] Anhydrous calcium chloride was added to the polyferric sulfate system at a molar ratio of 1:0.1, and titanyl sulfate was added to the system at a mass ratio of 1:0.05. The reaction was stirred at 55°C for 60 minutes, and the obtained liquid product was vacuum dried at 60°C for 48 hours to obtain a calcium-based polyferric titanium sulfate solid product.

[0075] The various indicators of the obtained solid product were analyzed according to the method specified in GB / T 14591-2016, among which the reducing substances (Fe 2+ The mass fraction of total iron is 18.58%, the basicity is 16.20%, and the turbidity removal rate is 78.96%.

[0076] By comparing the product performance indicators of Examples 1 to 6 and Comparative Example 1, it can be seen that when the calcium-iron ratio and the titanium-iron ratio exceed the range of the calcium-iron molar ratio of 1:0.01 to 0.09 and the titanium-iron mass ratio of 1:0.01 to 0.04, the coagulation effect of the modified product prepared with FeSO4·H2O as raw material is significantly reduced, and the turbidity removal rate is lower than the commercial level.

[0077] The liquid product of polyferric sulfate is prepared from ferrous iron as raw material.

[0078] Example 7

[0079] The polyferric sulfate system used in this embodiment is prepared using ferrous yellow, a by-product of titanium dioxide produced by the sulfuric acid process, as the iron raw material.

[0080] Anhydrous calcium chloride was added to the polyferric sulfate system at a molar ratio of 1:0.01, and the reaction was stirred at 55° C. for 90 minutes. The obtained liquid product was vacuum dried at 60° C. for 48 hours to obtain a calcium-based polyferric titanium sulfate solid product.

[0081] The various indicators of the obtained solid product were analyzed according to the method specified in GB / T 14591-2016, among which the reducing substances (Fe 2+ The mass fraction of total iron is 0.012%, the mass fraction of total iron is 19.90%, and the basicity is 14.65%, all of which meet the requirements of first-class products in GB / T 14591-2016. The turbidity removal rate is 91.25% and the coagulation effect is excellent after the sewage treatment effect evaluation.

[0082] Example 8

[0083] The polyferric sulfate system used in this embodiment is prepared using ferrous yellow, a by-product of titanium dioxide produced by the sulfuric acid process, as the iron raw material.

[0084] Calcium chloride dihydrate was added to the polyferric sulfate system at a molar ratio of 1:0.02, and the mixture was stirred and reacted at 70° C. for 30 min. The obtained liquid product was vacuum dried at 80° C. for 24 h to obtain a calcium-based polyferric titanium sulfate solid product.

[0085] The various indicators of the obtained solid product were analyzed by referring to the method specified in GB / T 14591-2016, and all of them met the requirements of the first-class product in GB / T14591-2016. The turbidity removal rate was 89.05% after the sewage treatment effect evaluation. Compared with Example 7, the calcium source in this example was added excessively, resulting in a decrease in the turbidity removal rate.

[0086] Example 9

[0087] The polyferric sulfate system used in this embodiment is prepared using ferrous yellow, a by-product of titanium dioxide produced by the sulfuric acid process, as the iron raw material.

[0088] Anhydrous calcium chloride was added to the polyferric sulfate system at a molar ratio of 1:0.04, and the reaction was stirred at 60° C. for 60 min. The obtained liquid product was vacuum dried at 70° C. for 36 h to obtain a calcium-based polyferric titanium sulfate solid product.

[0089] The various indicators of the obtained solid product were analyzed by referring to the method specified in GB / T 14591-2016, and all of them met the requirements of the first-class product in GB / T14591-2016. The turbidity removal rate was 86.31% after the sewage treatment effect evaluation. Compared with Example 8, the calcium source in this example was further increased, resulting in a decrease in the turbidity removal rate.

[0090] Based on the performance indicators of Examples 7 to 9, within the range of calcium-iron ratio of 0.01 to 0.04, the turbidity removal rate of the product was greater than 85%, and the coagulation effect was relatively excellent.

[0091] Example 10

[0092] The polyferric sulfate system used in this embodiment is prepared using ferrous yellow, a by-product of titanium dioxide produced by the sulfuric acid process, as the iron raw material.

[0093] Anhydrous calcium chloride was added to the polyferric sulfate system at a molar ratio of 1:0.07, and the reaction was stirred at 55° C. for 60 min. The obtained liquid product was vacuum dried at 60° C. for 48 h to obtain a calcium-based polyferric titanium sulfate solid product.

[0094] The various indicators of the obtained solid product were analyzed by referring to the method specified in GB / T 14591-2016, and all of them met the requirements of the first-class product in GB / T14591-2016. The turbidity removal rate was 82.79% after the sewage treatment effect evaluation. Compared with Example 9, the calcium source in this example was further increased, and the turbidity removal rate of the product did not increase further, but decreased instead.

[0095] Embodiment 11

[0096] The polyferric sulfate system used in this embodiment is prepared using ferrous yellow, a by-product of titanium dioxide produced by the sulfuric acid process, as the iron raw material.

[0097] Anhydrous calcium chloride was added to the polyferric sulfate system at a molar ratio of 1:0.09, and the mixture was stirred and reacted at 55° C. for 60 min. The obtained liquid product was vacuum dried at 60° C. for 48 h to obtain a calcium-based polyferric titanium sulfate solid product.

[0098] The various indicators of the obtained solid product were analyzed by referring to the method specified in GB / T 14591-2016, and all of them met the requirements of the first-class product in GB / T14591-2016. The turbidity removal rate was 81.64% after the sewage treatment effect evaluation. Compared with Example 10, the calcium source in this example was further increased, and the turbidity removal rate of the product was further reduced.

[0099] Comparative Example 5

[0100] Dissolve ferrous iron in water and put it into a reactor with iron powder in a molar ratio of 1:0.24, stir and react at 55°C for 15 minutes, add 30% (mass fraction) hydrogen peroxide solution to the system at a mass ratio of 1:0.4, stir and react at 55°C for 90 minutes, add 0.1 mol 98% (mass fraction) sulfuric acid to the system at 80 minutes of reaction to obtain a liquid product of polyferric sulfate. The obtained liquid product is vacuum dried at 60°C for 48 hours to obtain a solid product of polyferric sulfate.

[0101] The various indicators of the obtained solid product were analyzed according to the method specified in GB / T 14591-2016, among which the reducing substances (Fe 2+ The mass fraction of total iron is 19.94%, the basicity is 11.48%, and the turbidity removal rate is 80.20% after sewage treatment effect evaluation.

[0102] By comparing the product performance indicators of Examples 7 to 11, it can be seen that within the range of calcium-iron molar ratio of 0.01 to 0.09, the product with ferrous iron as raw material modified by titanium calcium has a better degree of polymerization, a significantly improved turbidity removal rate, and a better coagulation effect than the unmodified product.

[0103] Comparative Example 6

[0104] The polyferric sulfate system used in this embodiment is prepared using ferrous yellow, a by-product of titanium dioxide produced by the sulfuric acid process, as the iron raw material.

[0105] Anhydrous calcium chloride was added to the polyferric sulfate system at a molar ratio of 1:0.1, and the mixture was stirred and reacted at 55° C. for 60 min. The obtained liquid product was vacuum dried at 60° C. for 48 h to obtain a calcium-based polyferric titanium sulfate solid product.

[0106] The various indicators of the obtained solid product were analyzed according to the method specified in GB / T 14591-2016, among which the reducing substances (Fe 2+ The mass fraction of total iron is 18.70%, the basicity is 16.35%, and the turbidity removal rate is 77.98% after sewage treatment effect evaluation.

[0107] By comparing the product performance indicators of Examples 7 to 11 and Comparative Example 5, it can be seen that when the calcium-iron molar ratio exceeds the range of 0.01 to 0.09, the coagulation effect of the modified product prepared with ferrous iron as raw material decreases significantly, and the turbidity removal rate is lower than that of the unmodified product.

[0108] This application is described in detail for the purpose of enabling those skilled in the art to understand the contents of this application and implement them. This is not intended to limit the scope of protection of this application. Any equivalent changes or modifications made according to the spirit of this application should be included in the scope of protection of this application.

Claims

1. A method for preparing calcium-based polyferric titanium sulfate, characterized in that The following steps are involved: S1. Adding a calcium-based modifier and a titanium-based modifier to a polymerized ferric sulfate liquid product for modification, heating and stirring to obtain a modified liquid product; S2. Drying the liquid product obtained in step S1 to prepare solid calcium-based polyferric titanium sulfate.

2. The preparation method according to claim 1, characterized in that: The molar ratio of the calcium-based modifier to the iron raw material for preparing the polyferric sulfate liquid product is 1:0.01-0.04; the mass ratio of the titanium-based modifier to the iron raw material for preparing the polyferric sulfate liquid product is 1:0.001-0.

04.

3. The preparation method according to claim 1 or 2, characterized in that: The calcium-based modifier is selected from one or more of anhydrous calcium chloride, dihydrate calcium chloride, calcium oxide, and calcium hydroxide.

4. The preparation method according to claim 1 or 2, characterized in that: The titanium-based modifier is selected from one or more of titanyl sulfate, metatitanic acid, titanium chloride, titanium dioxide, and titanium powder.

5. The preparation method according to claim 1, characterized in that: The heating temperature for modification in step S1 is 55-70° C., and the reaction time is 20-90 min; the drying temperature in step S2 is 60-80° C., and the drying time is 24-48 h.

6. A method for preparing calcium-based polyferric titanium sulfate, characterized in that The following steps are involved: S0, dissolving the yellow ferrous iron produced as a by-product of the sulfuric acid process titanium dioxide in water, adding an iron source and stirring, then adding an oxidant, heating and stirring, and performing oxidation, hydrolysis, and polymerization reactions to obtain a liquid polymerized ferric sulfate product; S1. Adding a calcium-based modifier to a polyferric sulfate liquid product, heating and stirring to obtain a modified liquid product; S2. Drying the liquid product obtained in step S1 to prepare solid calcium-based polyferric titanium sulfate.

7. The preparation method according to claim 6, characterized in that: The molar ratio of the calcium-based modifier to ferrous iron is 1:0.01-0.

04.

8. The preparation method according to claim 6 or 7, characterized in that: The calcium-based modifier is selected from one or more of anhydrous calcium chloride, dihydrate calcium chloride, calcium oxide, and calcium hydroxide.

9. The preparation method according to claim 6, characterized in that: The heating temperature for modification in step S1 is 55-70° C., and the reaction time is 20-90 min; the drying temperature in step S2 is 60-80° C., and the drying time is 24-48 h.

10. Calcium-based poly-iron titanium sulfate prepared by the method according to any one of claims 1 to 9.